Role of Proliferative Marker (Ki-67) and ER, PR in Cervical Epithelial Lesions with Clinicopathological Association: A Cross-sectional Study - Shrabani Mitra; Deepankar Shriwas; Madhumita Mondal; Gouri Sankar Kamilya; Asim Kumar Manna (Journal of Clinical and Diagnostic Research)
Introduction: Cervical cancer is the fourth most common cancer affecting women worldwide, following breast, colorectal and lung cancer. India contributes 28% of the cervical cancer mortality burden, with 87,090 deaths due to cervical cancer, making it the second most populous country in the world. Oestrogen Receptors (ER) are located not only in the tissues of the female reproductive tract and breast but also in diverse tissues such as bone, brain, liver, colon, skin and salivary glands. Ki-67 is a nuclear protein expressed during all active phases of the cell cycle and is absent in the G0 phase, making it a potent biomarker of cellular proliferation. Aim: To study the clinicopathological spectrum of cervical epithelial lesions and their association with cell proliferation (Ki67) and ER and Progesterone Receptor (PR) status. Materials and Methods: This was a single-institution-based cross-sectional study in which a total of 202 cases of cervical epithelial lesions diagnosed from May 2022 to May 2024 at the Institute of Post Graduate Medical Education and Research and SSKM Hospital, Kolkata, West Bengal, India were studied. Clinical and demographic data were associated with histological findings. Immunohistochemical staining with Ki-67, ER and PR antibodies was performed and the Ki-67 labelling index and ER and PR status were assessed respectively. Based on the assessment, a master chart was prepared for patients belonging to different age groups with certain medical complaints, and data were organised into tables. Statistical analysis was conducted using Microsoft Excel and Statistical Package for the Social Sciences (SPSS) version 23.0 software. Results: In this study, 202 patients were evaluated. The patient age ranged from 18 to 68 years, with a mean age of 40.78±10.13 years. Cervical epithelial lesions were most prevalent in the age group of 31 to 50 years (66.8%). Among the 202 cases, 108 (53.5%) were non neoplastic, 10 cases (5.0%) were benign neoplastic, and 84 cases (41.6%) were malignant neoplastic lesions. The difference in proliferative rates, as indicated by the Ki-67 labelling index, between benign neoplasms and malignant neoplasms was statistically significant (p-value <0.001). There was no significant association between the levels of ER and the nature of the lesions in the patients (non neoplastic and neoplastic) (p-value=0.08). Additionally, there was no significant association between the levels of PR and the nature of the lesions in the patients (p-value=0.25). Conclusion: Malignant neoplasms exhibit a significantly higher proliferative rate than benign neoplasms and non neoplastic lesions. No significant association between ER and PR status and the nature of the lesions was found in the study, although the mean ER score and mean PR score of adenocarcinomas were significantly higher than those of Squamous Cell Carcinoma (SCC) and Cervical Intraepithelial Neoplasia (CIN).